The Influence of Effective Communication, Work Motivation and Work Discipline on Employee Work Productivity in Emping Blinjo Msmes in Kediri - Dewi, Anita Sumelvia; Sudarmiatin; Wardana, Ludi Wishnu (Asian Journal of Management Analytics, 2023)
The aim of this research is to find out and explain effective communication, work motivation and work discipline which simultaneously have a significant effect on employee work productivity. This type of research uses quantitative research. The data sources in this research use primary and secondary data. The sample in the research was 40 employees of MSMEs Emping Blinjo using saturated sampling techniques. The analysis techniques used are validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, t test, F test, multiple linear regression analysis, and coefficient of determination (R2) test using the SPSS version 25 program. Research results partially the effective communication variable has a positive and significant effect on employee work productivity, the work motivation variable has a positive and significant effect on employee work productivity, and the work discipline variable has a positive and significant effect on employee work productivity. Simultaneously the variables of effective communication, work motivation and discipline work has a significant effect on employee work productivity at Emping Blinjo MSMEs.